Correlation of self-control with aggressive behavior of adolescent motorcyclists - Ilham Nur Alfian, Setia Budi, (Opción, 2020)
Most of road accidents are caused by aggressive behavior of motorcyclists, especially adolescents. An understanding of self-control is needed to reduce the risk of accidents. This study aimed to determine a relationship between self-control and aggressive behavior of motorcyclists in adolescents. The results of the correlation test between two variables indicated that the significance of the variable self-control driving with driver aggressiveness was 0.000. The correlation coefficient obtained was negative which showed the direction of the opposite relationship so that when self-control of motorbike driving was high then aggressive behavior was also high.